Borneo Group : Achieving Quantum Leap Growth Through Forward Integration - Loon, Cheng Heng (2003)
This paper traces the history of Borneo Group, the internal and external environments in which it operates, its strengths, weaknesses, opportunities and threats and finally the strategies it employs in its core competencies to reposition itself in the automotive parts industry in order to obtain above-average returns.